Night Work, Rotating Shift Work, and the Risk of Cancer in Japanese Men and Women: The JACC Study - Ahmed Arafa; Ehab S Eshak; Hiroyasu Iso; Isao Muraki; Akiko Tamakoshi (Journal of Epidemiology, 2021)
Background: Limited epidemiological evidence has suggested a positive relationship between night shift work and the risk of cancer. Herein, we investigated the prospective association between different forms of work schedule and the risk of numerous cancers and all-cause cancer among Japanese men and women. Methods: This cohort study included 45,390 working men and women aged 40–79 years and registered in the Japan Collaborative Cohort Study (JACC Study). The Cox proportional hazards models were used to calculate the hazard ratios (HRs) and their 95% confidence intervals (CIs) for incident cancer among those who reported engagement in night work and rotating shift work for their longest occupations compared with day work. Results: Within a median follow-up duration of 14.2 years, 2,283 (9.4%) men and 1,309 (4.5%) women developed cancer. Among men, rotating shift work was significantly associated with increased risk of esophageal cancer (HR 2.47; 95% CI, 1.42–4.31) and decreased risk of liver cancer (HR 0.54; 95% CI, 0.30–0.98). Also, rotating shift work tended to be associated with the increased risk of prostate cancer (HR 1.42; 95% CI, 0.95–2.12). Night work and rotating shift work were not related to the risk of all-cause cancer in either sex. Conclusion: Rotating shift work might contribute to the increased risk of esophageal cancer and prostate cancer and the decreased risk of liver cancer among Japanese men.